Obstructive Sleep Apnea and Hearing Loss: Is There Any Correlation? - Pankaj Chauhan; Trilok Chand Guleria; Sunil Sharma; Ravinder S. Minhas; Madhuri Dadwal; Narender K. Mohindroo (International Archives of Otorhinolaryngology, 2023)
Introduction Obstructive sleep apnea (OSA) is a breathing disorder related to sleep that has a negative effect on the behavior and health of people around the globe. Chronic hypoxemia and variations in the concentration of oxygen in the blood noticed in OSA individuals may have adverse effects on the process of auditory transduction and transmission.